Clinical and genetic interpretation of uncertain DMD missense variants: evidence from mRNA and protein studies - Zhiying Xie; Chang Liu; Haiyan Yu; Zhihao Xie; Chengyue Sun; Ying Zhu; Xiaoyu Hu; Li Bai; Luhua Wei; Peng Sun; Yanyu Lu; Yunlong Lu; et al. (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Pathogenic missense variants in the dystrophin (DMD) gene are rarely reported in dystrophinopathies. Most DMD missense variants are of uncertain significance and their pathogenicity interpretation remains complicated. We aimed to investigate whether DMD missense variants would cause aberrant splicing and re-interpret their pathogenicity based on mRNA and protein studies. Methods Nine unrelated patients who had an elevated serum creatine kinase level with or without muscle weakness were enrolled. They underwent a detailed clinical, imaging, and pathological assessment. Routine genetic testing and muscle-derived mRNA and protein studies of dystrophin and sarcoglycan genes were performed in them. Results Three of the 9 patients presented with a Duchenne muscular dystrophy (DMD) phenotype and the remaining 6 patients had a suspected diagnosis of Becker muscular dystrophy (BMD) or sarcoglycanopathy based on their clinical and pathological characteristics. Routine genetic testing detected only 9 predicted DMD missense variants in them, of which 6 were novel and interpreted as uncertain significance. Muscle-derived mRNA studies of sarcoglycan genes didn’t reveal any aberrant transcripts in them. Dystrophin mRNA studies confirmed that 3 predicted DMD missense variants (c.2380G > C, c.4977C > G, and c.5444A > G) were in fact splicing and frameshift variants due to aberrant splicing. The 9 DMD variants were re-interpreted as pathogenic or likely pathogenic based on mRNA and protein studies. Therefore, 3 patients with DMD splicing variants and 6 patients with confirmed DMD missense variants were diagnosed with DMD and BMD, respectively. Conclusion Our study highlights the importance of muscle biopsy and aberrant splicing for clinical and genetic interpretation of uncertain DMD missense variants.